Measure pseudo almost periodic solutions for differential equations with reflection. Issue 3 (11th February 2022) - Miraoui, Mohsen
ABSTRACT: In this research paper, we give some new results for the existence and uniqueness of doubly measure pseudo almost periodic (Or ( μ, ν ) -pap) solutions for some differential equations with reflection. We will use the Banach fixed-point theorem and some properties of pseudo almost periodic functions with measurements and we will discuss both linear and nonlinear cases. Finally, we finish with some applications to illustrate our results.